Ergogenic effect of dietary nitrates in female swimmers - Pospieszna, Barbara; Wochna, Krystian; Jerszyński, Damian; Gościnna, Katarzyna; Czapki, Janusz (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. A diet enriched with inorganic nitrates by increasing nitrite plasma levels, has been described to benefit exercise performance, blood pressure, endothelial function, and other body functions. It was also proven that additional dietary polyphenols, e.g. red wine or fruits such as strawberries, currants and berries, significantly stimulate the NO3- – NO2- – NO metabolic pathway. Aim of Study. A double-blind crossover study was performed to evaluate the influence of 8-day nitrate-rich (5.1 mmol NO3- )juice supplementation (C – carrot juice versus B/A – beetroot juice with chokeberry addition) on blood pressure and exercise tolerance in female swimmers. Material and Methods. Eleven female swimmers volunteered for the study (age 20.9 ± 1.3 years). A two-part freestyle swimming exercise test was performed: the anaerobic part consisting of six 50 meter maximal sprints, and the endurance part consisting of an 800 meter continuous swim. Blood Pressure (BP) and Heart Rate (HR) at rest, performance time of all the distances, and peak HR after both test parts were assessed. Results. There were no significant differences in blood pressure and heart rate at rest between two measurement terms. Improvements in 50 meter sprint performance were noted in later repetitions (3-6) of the anaerobic part of the test, and they were more pronounced after B/A juice supplementation. The significant increase in the 800 meter freestyle swim performance was obtained after consuming both juices. However, during C juice supplementation this improvement was accompanied by a significant increment in peak heart rate. Conclusions. 8-daysupplementation with beetroot juice with chokeberry addition increases exercise tolerance in both, repeated, maximal and endurance swims. Ergogenic effects of carrot juice with a high nitrate content seem to be possible in young female swimmers, but they still require further research
Keywords: high-nitrate diet; beetroot; carrot; exercise tolerance